Waste Identification Using the Value Stream Mapping (VSM) Method on the PT XYZ Transparent Bar Soap Production Line - Imtinan Imtinan; Bunga Cahyaputri (Politeknik STMI Jakarta, 2024)
The production process is an activity to create or increase the function of a good or service by using existing factors such as human resources, machines, materials and money to make it more useful for human needs. PT XYZ is a cosmetic manufacturing services company that has been established for more than 15 years producing quality cosmetics, skincare and beauty soap. However, during the production process there were various problems, namely waste was found. The aim of this research is to identify waste and provide suggestions for improvements to PT XYZ's transparent bar soap production line. The method used in this research is Value Stream Mapping (VSM) by conducting interviews and direct observation as a data collection method. The results of the research that has been carried out are the discovery of waste in the form of transportation, waiting, and defects caused by various factors. These factors include human factors, methods, machines, processes and the environment. From the identification results, several recommendations for improvement were proposed, such as holding training on the use of sealing machines, implementing the 5R culture, routinely checking raw materials, optimizing the use of cutting machines, and routinely monitoring products and employee activities. After carrying out the improvement process, the production time was 2,581.36 minutes with a lead time of 26.29 minutes, compared to the initial condition, which was 4,102 minutes with a lead time of 39.89 minutes. Thus, it can be concluded that after carrying out the improvement process, it is hoped that the production process will run faster than before.